Novel potent inhibitors of A. thaliana cytokinin oxidase/dehydrogenase - Zatloukal, Marek; Gemrotová, Markéta; Dolezal, Karel; Havlícek, Libor; Spíchal, Lukás; Strnad, Miroslav (Bioorganic & medicinal chemistry, 2008)
The synthesis of a new group of 2-X-6-anilinopurines, including compounds with potential cytokinin-like activities, with various substitutions (X=H, halogen, amino, methylthio or nitro) on the phenyl ring is described. The prepared compounds have been characterized using standard physico-chemical methods, and the influence of individual substituents on biological activity has been compared in three different bioassays, based on the stimulation of tobacco callus growth, retention of chlorophyll in excised wheat leaves and the dark induction of betacyanin synthesis in Amaranthus cotyledons. The biological activity of the prepared compounds was also assessed in receptor assays, in which the ability of the compounds to activate the cytokinin receptors AHK3 and AHK4/CRE1 was studied. Finally, the interactions of the compounds with the Arabidopsis cytokinin oxidase/dehydrogenase AtCKX2 (heterologously expressed) were investigated. Systematic testing led to the identification of two very potent inhibitors of AtCKX2: 2-chloro-6-(3-methoxyphenyl)aminopurine and 2-fluoro-6-(3-methoxyphenyl)aminopurine.
Keywords: Structure-Activity Relationship; molekulární struktura; vztahy mezi strukturou a aktivitou; Molecular Structure; adenin; inhibitory enzymů; Enzyme Inhibitors; Oxidoreductases; Adenine; Arabidopsis; oxidoreduktasy